2003
DOI: 10.1089/107555303322524517
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acupuncture or Acupressure on Quality of Life of Patients with Chronic Obstructive Asthma: A Pilot Study

Abstract: Patients with clinically stable, chronic obstructive asthma experienced clinically significant improvements in quality of life when their standard care was supplemented with acupuncture or acupressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
46
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 19 publications
1
46
0
Order By: Relevance
“…23 Likewise, a study examining the effects of acupuncture and acupressure on quality of life in patients with chronic obstructive asthma showed an 18.5% and 6.5% improvement, respectively, in quality of life for these treatments. 24 Potentially, the discrepancies in the degree of change in the quality of life scores between these studies may be due to differences in the severity of asthma between the study groups, but the present study clearly indicates that yoga training improves quality of life in those with mild-to-moderate asthma.…”
mentioning
confidence: 51%
See 1 more Smart Citation
“…23 Likewise, a study examining the effects of acupuncture and acupressure on quality of life in patients with chronic obstructive asthma showed an 18.5% and 6.5% improvement, respectively, in quality of life for these treatments. 24 Potentially, the discrepancies in the degree of change in the quality of life scores between these studies may be due to differences in the severity of asthma between the study groups, but the present study clearly indicates that yoga training improves quality of life in those with mild-to-moderate asthma.…”
mentioning
confidence: 51%
“…These improvements in quality of life with yoga training were greater than previously reported in studies using drug therapy 23 or other types of alternative medicine. 24 A study examining the effect of the inhaled anti-inflammatory agent Nedocromil demonstrated an 8-unit improvement in patients' SGRQ score. 23 Likewise, a study examining the effects of acupuncture and acupressure on quality of life in patients with chronic obstructive asthma showed an 18.5% and 6.5% improvement, respectively, in quality of life for these treatments.…”
mentioning
confidence: 99%
“…The practical advantages of AA include 32,33 : (1) only minimal equipment is needed and any physicians or nurses can perform this treatment; (2) physicians as well as other health care providers who have rare or no experience in traditional Chinese medicine can learn this technique within a few hours and can use it whenever indicated; (3) it is almost a ''no-cost'' intervention; (4) AA is non-invasive and does not affect the integrity of the epidermis. Acupressure, including AA, has been found to be safe and effective in decreasing prehospital anxiety 32 , reducing preoperative anxiety 34,35 , alleviating stress 33 and improving quality of life 36,37 . IVF is usually the final treatment option for infertile couples, and failure will probably mean their remaining childless 38 .…”
Section: Discussionmentioning
confidence: 99%
“…6 Tsay et al 7 found that massage of pressure points was effective in improving the sleep quality and life quality of end-stage renal patients. Maa et al 8 also showed a significant improvement in the life quality of patients with asthma with acupressure. Three other research teams reported the positive role of acupressure in the Shenmen point of the wrists on the sleep quality of patients.…”
Section: Introductionmentioning
confidence: 91%